Behavior of Photovoltaic during the Partial Solar Eclipse in Bandung. (March 2017) - Nandiyanto, A B D; Rusli, A; Purnamasari, A; Abdullah, A G; Riza, L S
Abstract: The purpose of this study was to investigate the behavior of photovoltaic system during the partial solar eclipse phenomenon of 9 March 2016 in Bandung, Indonesia. In the experimental method, we monitored the impact of the solar eclipse on the photovoltaic system in solar cell system. To qualitatively explain the experimental observations, we compared the behavior of photovoltaic system in the solar eclipse day (9 March 2016) with the two sunny days (8 and 10 March 2016). The experimental results showed that the intensity and electricity power increased along with the solar light irradiation time. However, when there is a solar eclipse phenomenon, the intensity and electricity power is suddenly down.